Obesity Prevention and National Food Security: A Food Systems Approach. (29th November 2012) - Finney Rutten, Lila; Yaroch, Amy Lazarus; Patrick, Heather; Story, Mary
Abstract : Interventions that cultivate sustainable food systems to promote health, prevent obesity, and improve food security have the potential for many large-scale and long-lasting benefits including improvements in social, environmental, health, and economic outcomes. We briefly summarize findings from previous research examining associations between obesity and food insecurity and discuss the need for greater synergy between food insecurity initiatives and national obesity prevention public health goals in the United States. The common ground between these two nutrition-related public health issues is explored, and the transformation needed in research and advocacy communities around the shared goal of improving population health through individual, environmental, and policy level changes to promote healthy sustainable food systems is discussed. We propose an ecological framework to simultaneously consider food insecurity and obesity that identifies levers for change to promote sustainable food systems to improve food security and prevent obesity.